Research on the Impact of Challenge-Hindrance Stress on Employees’ Innovation Performance: A Chain Mediation Model - Cai, Wei; Xu, Chao; Yu, Shengxian; Gong, Xiaoxiao (Frontiers in Psychology, 2022)
Based on the transaction theory of stress and the theory of resource conservation, which introduces knowledge acquisition and intrinsic motivation as mediating variables, a chain mediating model for the influence of challenge-hindrance stress on innovation performance is constructed. Data of 295 samples collected in three stages were used to testify hypothesis. The results confirmed a positive relationship between challenge stress and innovation performance, and a negative relationship between hindrance stress and innovation performance. Intrinsic motivation and knowledge acquisition play a parallel and chain mediating role in the relationship between challenge-hindrance stress and innovation performance. These findings contribute to a deeper understanding of how challenge -hindrance stress affects innovation performance and provide important practical guidance for improving innovation performance.